Uneasy Bedfellows: Comparing the diversity of German public service news on television and on Facebook. Issue 1 (2nd January 2019) - Steiner, Miriam; Magin, Melanie; Stark, Birgit
Abstract : News consumption has shifted increasingly to new platforms and gateways such as social network sites (SNS) with Facebook leading the way. Accordingly, journalists must cope with this "uneasy bedfellow" and provide news on Facebook to attract otherwise hard-to-reach audiences. This is even more relevant for public service broadcasters (PSBs), whose mission is to serve the interests and needs of every citizen. Bound to their public service mission, PSBs have to generally fulfill specific normative requirements such as diversity within their coverage, particularly to a higher degree than their commercial counterparts. Consequently, these requirements should be transferred to public service online supply in general and to public service supply on platforms such as Facebook. Whereas these demands have at best been roughly discussed, they have not been investigated to date. Therefore, we conducted a content analysis of the most viewed public service and commercial German TV newscasts and their respective Facebook sites, and analyzed whether public service news outperform commercial news on Facebook and whether they perform as good as on TV in terms of diversity (diversity of issues and of people and groups). Results show that public service news on Facebook show an even higher performance (albeit slightly) than on television.